2021
DOI: 10.4239/wjd.v12.i7.1057
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive overview of human serum albumin glycation in diabetes mellitus

Abstract: The presence of excess glucose in blood is regarded as a sweet hurt for patients with diabetes. Human serum albumin (HSA) is the most abundant protein in human plasma, which undergoes severe non-enzymatic glycation with glucose in patients with diabetes; this modifies the structure and function of HSA. Furthermore, the advanced glycation end products produced by glycated HSA can cause pathological damage to the human body through various signaling pathways, eventually leading to complications of diabetes. Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 109 publications
(130 reference statements)
1
17
0
Order By: Relevance
“…2 C. The concentration-dependent activity can be seen even in PM (36–65%) and increases significantly to 52–91% inhibition as a result of FPM. Albumin is abundant in serum and can be glycated at multiple sites, particularly in patients with diabetes mellitus ( Qiu et al, 2021 ). The effect of the extracts on all protein glycation stages was determined by the BSA-Fru model system ( Wang et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…2 C. The concentration-dependent activity can be seen even in PM (36–65%) and increases significantly to 52–91% inhibition as a result of FPM. Albumin is abundant in serum and can be glycated at multiple sites, particularly in patients with diabetes mellitus ( Qiu et al, 2021 ). The effect of the extracts on all protein glycation stages was determined by the BSA-Fru model system ( Wang et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…SiteMap was utilized to assess and forecast the binding pocket for ligand attachment (Figure 2). Together with amino acids from previously published literature, the most efficient binding site was identified as follows 40,41 : Tyr 149, Arg 194, Arg198, Ser 191, Trp 213, Ser 214, Arg 217, Lys 221, Leu 237, His 241, Arg 256, Leu 259, Ala 290, Glu 291, and Lys 294 residues.…”
Section: Resultsmentioning
confidence: 99%
“…SiteMap was utilized to assess and forecast the binding pocket for ligand attachment (Figure 2). Together with amino acids from previously published literature, the most efficient binding site was identified as follows 40,41…”
Section: Sitemap Analysismentioning
confidence: 99%
“…Subdomain I (A and B) is composed of residues 1–195, while II (A and B) spans from 196 to 383 and III (A and B) spans from 384 to 585. , It has been reported that the ligand (drug/compound) is mainly transported via binding through Sudlow sites II and III. Sudlow site I is located in subdomain IIA and Sudlow site II is located in subdomain IIIA . Molecular docking results also confirm this observation as compounds 1–4 interacted with different amino acids of the Sudlow sites II and III.…”
Section: Resultsmentioning
confidence: 99%